Nutrition security in urban areas of Latin America - Sanchez-Grinan, Maria Ines (International Food Policy Research Institute, 1998)
The population of Latin America is now largely urban. By 1990, 72 percent of the people of the region were living in cities. By 2020, the urban population could reach 83 percent. With increasing urbanization, the region faces problems of poverty, nutrition, and health that are somewhat different from those when the population was more rural. By paying special attention to the interactions of malnutrition with health and involving individuals and the community in development of new local-level networks for provision of care, Latin American cities can make significant progress toward eradicating malnutrition and food insecurity by the year 2020.